Midbody-Localized Aquaporin Mediates Intercellular Lumen Expansion During Early Cleavage of an Invasive Freshwater Bivalve - Zieger, Elisabeth; Schwaha, Thomas; Burger, Katharina; Bergheim, Ina; Wanninger, Andreas; Calcino, Andrew D. (Frontiers in Cell and Developmental Biology, 2022)
Intercellular lumen formation is a crucial aspect of animal development and physiology that involves a complex interplay between the molecular and physical properties of the constituent cells. Embryos of the invasive freshwater mussel Dreissena rostriformis are ideal models for studying this process due to the large intercellular cavities that readily form during blastomere cleavage. Using this system, we show that recruitment of the transmembrane water channel protein aquaporin exclusively to the midbody of intercellular cytokinetic bridges is critical for lumenogenesis. The positioning of aquaporin-positive midbodies thereby influences the direction of cleavage cavity expansion. Notably, disrupting cytokinetic bridge microtubules impairs not only lumenogenesis but also cellular osmoregulation. Our findings reveal a simple mechanism that provides tight spatial and temporal control over the formation of luminal structures and likely plays an important role in water homeostasis during early cleavage stages of a freshwater invertebrate species.